ZSTK474, a novel phosphatidylinositol 3-kinase inhibitor identified using the JFCR39 drug discovery system - Kong De-xin; Yamori Takao (Acta Pharmacologica Sinica, 2016)
JFCR39 is an informatic anticancer drug discovery system that utilizes a panel of 39 human cancer cells coupled with a drug-activity database. This system not only provides disease-oriented information but can also predict the mechanism of action of a given antitumor agent. Development of a phosphatidylinositol 3-kinase (PI3K) inhibitor as an anticancer drug candidate has attracted a great deal of attention from both academia and industry because PI3K is known to be closely involved in carcinogenesis. ZSTK474 was identified as a PI3K inhibitor using JFCR39 system in combination with COMPARE analysis program. These findings were based on the similar fingerprint (growth inhibition profiles for JFCR39 human cancer cell line panel) with that of a classical PI3K inhibitor LY294002. Biochemical experiments confirmed ZSTK474 to be a potent pan-class I PI3K inhibitor, with high selectivity over other classes of PI3K and protein kinases. We previously reported the in vitro and in vivo antitumor efficacy of ZSTK474, together with the G0/G1 arrest and antiangiogenic activity. Here, we review the JFCR39 system and summarize recent studies on PI3K biology and the development of PI3K inhibitors before discussing ZSTK474 in some detail.